Special eccentric vertices for chordal and dually chordal graphs and related classes - De Caria, Pablo Jesús (2009)
It is known that any vertex of a chordal graph has an eccentric vertex which is simplicial. Here we prove similar properties in related classes of graphs where the simplicial vertices will be replaced by other special types of vertices.